Estuarine Mixing Patterns and Siltation Impact: A Case Study of Air Rami River Estuary: Pola Pencampuran Muara dan Dampak Pendangkalan: Studi Kasus Muara Sungai Air Rami - Reva Marlita Putri; Supiyati Supiyati; Suwarsono Suwarsono (Universitas Muhammadiyah Sidoarjo, 2023)
Investigating the Air Rami River Estuary in Mukomuko Regency, this study examines the influence of siltation on mixing characteristics within the estuarine environment. The research aims to discern and characterize mixing patterns in the estuary, employing direct field measurements conducted during both tide and low tide conditions in March 2023. Descriptive and quantitative analyses reveal notable salinity variations, with tidal conditions exhibiting a peak salinity of 10 ppt at a depth of 2 meters, and low tide conditions showing a maximum salinity of 5 ppt at 1.5 meters depth. Temperature variations are also observed, with tide conditions reaching 31.5°C and low tide conditions at 27.2°C. Calculation of the estuary number indicates a perfectly mixed stratified estuary mixing type, characterized by an estuary number magnitude of 0.53. These findings offer insights into estuarine mixing dynamics and their implications for coastal ecosystems. Highlight: Siltation Impact: Investigates the influence of siltation on mixing patterns in the Air Rami River Estuary, Mukomuko Regency. Salinity and Temperature Variations: Describes notable variations in salinity and temperature during tide and low tide conditions, providing insights into estuarine dynamics. Estuary Number Analysis: Utilizes the estuary number to classify estuarine mixing type, revealing a perfectly mixed stratified estuary with implications for coastal ecosystems. Keyword: Estuarine Mixing, Siltation Influence, Salinity Variations, Temperature Dynamics, Coastal Ecosystems